Evaluasi Peran Forum Anak Kota Tanjung Pinang dalam Kebijakan Kota Layak Anak: Indonesia - Junriana; Yuliani, Nursalasati Putri; Siam, Nurbaiti Usman; Budiman, Shahril (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2022)
Fulfillment of children's rights must be carried out by the government for the continuity of future development. The problem with this research is that there are still many children whose rights have not been fulfilled, such as the lack of facilities and infrastructure in the field of participation towards a Child Friendly City. Many children in Tanjungpinang City do not know about the existence of a participation forum that is directly under the umbrella of the government. In a situation like this, the government has formed a forum such as the Tanjungpinang City Children's Forum to become an organization that can embrace and express the aspirations of the children in Tanjungpinang City. The Tanjungpinang City Children's Forum which was formed as an instrument to become a forum for children's participation refers to the Regulation of the Minister of Women's Empowerment for Child Protection of the Republic of Indonesia Number 18 of 2019 concerning the Implementation of the Children's Forum. The purpose of this study was to evaluate the role of the Tanjungpinang City Children's Forum in the Development of a Child Friendly City in Tanjungpinang City. The theory used is Daniel Stufflebeam's evaluation model, namely CIPP (Context, Input, Process, and Product) with a qualitative approach to evaluative methods. The results of this study indicate that the role of the Tanjungpinang City Children's Forum in the Child Friendly City Policy has been fulfilled for a small part of the fulfillment of children's rights. Keywords: Children's Forum, Role Evaluation, Child Friendly City.